Reflection in teacher education: issues emerging from a review of current literature - Beauchamp, Catherine (Reflective Practice, 2015)
Reflection has become an accepted component of teacher education programs. Yet the concept has been much criticized, in particular its role in improving professional practice. This paper provides an overview of persistent and emerging criticisms of reflection, as well as a discussion of approaches taken to reflection in the literature since 2005. Two issues, context and identity, are revealed as predominant in the recent discussions of reflection. Recommendations stemming from the literature for better understanding reflection and for enhancing its role in teacher education are outlined, and a commentary on the possible impacts of adopting these recommendations in teacher education is included.